Design of a Flood Detection System Using VL53L1X Sensor Based on SMS Gateway - Hais, Yosi Riduas; Hamganisyah, Fadhil Islah; Saputra, Edi (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2025)
Floods often occur suddenly, disrupting community activities, damaging infrastructure, and threatening human lives. Traditional flood monitoring methods, such as using rulers at dams or floodgates, are less effective because they cannot provide real-time alerts. Therefore, a more efficient and responsive system is needed. This research focuses on the design and development of a flood early detection system using the VL53L1X sensor integrated with an SMS Gateway. The system is capable of monitoring both water levels and rainfall in real-time and automatically sending notifications when potential flooding is detected. The study applies the ADDIE method—Analysis, Design, Development, Implementation, and Evaluation—to ensure systematic development and testing. Based on experimental results, the system successfully measured water levels and rainfall while sending SMS notifications. In the first test, the water level was 29.8 cm with 19.25 mm of rainfall, categorized as safe. In the second test, the water level rose to 59.9 cm with 45 mm of rainfall, generating a warning alert. The third test showed a water level of 81.5 cm and rainfall of 47.75 mm, categorized as danger. The system demonstrated reliable performance, with an average notification delay of just three seconds, proving effective for early flood detection